Skull Identification in Forensic Science- A Literature Review - Kamali, C; Murugan, D (International Journal of Computer Sciences and Engineering, 2025)
Human identification is one of the most noticeable disciplines in forensic medicine. To the area of Forensic Anthropology, identification task is performed by reviewing the skeletal remains. Over the past few decades, anthropologists have paid their attention on improving those techniques that allow a more precise identification. Hence, Forensic Identification has become a very active research area & Skull identification has been emerging as a vital field in this discipline. Skull Identification is drawing wide attention and been applied in huge number of forensic domains, ranging from the identification of victims of the Indian Ocean tsunami, Uttarakhand disaster to the recognition of terrorists. At present skull identification research points mainly on two categories. One is craniofacial superimposition and other is craniofacial reconstruction. In Craniofacial superimposition a photograph of a missing person is compared with a skull found to determine its identity. On the other hand, craniofacial reconstruction is concerned about getting a visual outlook of an individual where only skull and bone are remaining. These research topics are reviewed in this article.